2015
DOI: 10.3892/ol.2015.2872
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment platelet count as a predictor for survival and distant metastasis in nasopharyngeal carcinoma patients

Abstract: Abstract. The aim of the present study was to investigate the prognostic value of different pretreatment platelet (PLT) counts on the treatment outcome in nasopharyngeal carcinoma (NPC) patients receiving concurrent chemoradiotherapy (CCRT) or radiotherapy (RT) alone. A total of 1,501 NPC patients, including 412 receiving CCRT and 1,089 receiving RT, were enrolled in the present study. The PLT count cut-off points for the CCRT and RT groups were 150 and 300x10 9 /l, respectively, and the PLT counts were catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 38 publications
1
15
0
5
Order By: Relevance
“…Most studies reported that patients with high platelet counts showed poor prognosis. However, it is worth noting that Chen et al [24] found that patients those with lowest platelet counts (<150 × 10 9 ) also demonstrated poor OS; additionally, the OS of patients with highest platelet counts (>300 × 10 9 ) was not significantly lower than those with lowest platelet counts (<150 × 10 9 ). These inconsistent results across studies suggest that patients with a very low platelet count may also have a poor prognosis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies reported that patients with high platelet counts showed poor prognosis. However, it is worth noting that Chen et al [24] found that patients those with lowest platelet counts (<150 × 10 9 ) also demonstrated poor OS; additionally, the OS of patients with highest platelet counts (>300 × 10 9 ) was not significantly lower than those with lowest platelet counts (<150 × 10 9 ). These inconsistent results across studies suggest that patients with a very low platelet count may also have a poor prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies focused on metastatic NPC, [21,22,23,27] whereas 10 studies only included patients with nonmetastatic NPC. [1620,2426,28,29] The majority of studies assessed the patients’ hematologic parameters before treatment. NLR and lymphocyte counts were the most reported hematologic parameters, followed by PLR and LMR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 The neutrophil-tolymphocyte ratio (NLR) 5,[8][9][10][11] and the platelet-tolymphocyte ratio (PLR) 6,12,13 are biomarkers reflecting systemic inflammation that can be easily and inexpensively measured from a peripheral blood sample. 6,7 The neutrophil-tolymphocyte ratio (NLR) 5,[8][9][10][11] and the platelet-tolymphocyte ratio (PLR) 6,12,13 are biomarkers reflecting systemic inflammation that can be easily and inexpensively measured from a peripheral blood sample.…”
Section: Introductionmentioning
confidence: 99%